Evaluation of Trachelium Cultivars as Cut Flowers - RongNa Liang; Brent K. Harbaugh (EDIS, 2005)
Trachelium caeruleum has been grown in the United States as a cut flower for about a decade. Only two cultivars, 'White Umbrella' and 'Purple Umbrella', were readily available for commercial use before 1997, but nine new cultivars became available in the last few years. Comparative performance trials have been lacking for these cultivars in the United States. This trial evaluated 11 cultivars of Trachelium for cut flower production performance (vegetative and flowering characteristics) and postharvest longevity.  This document is HS991, one of a series of the Horticultural Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 20, 2004.